Characterization of ClpS2, an essential adaptor protein for the cyanobacterium Synechococcus elongatus - Tryggvesson, Anders; Ståhlberg, Frida M.; Töpel, Mats; Tanabe, Noriaki; Mogk, Axel; Clarke, Adrian K. (FEBS letters)
The adaptor protein ClpS associates to the Clp protease and promotes degradation of N-end rule substrates in eubacteria and in algal/plant chloroplasts. Cyanobacteria are unusual in having two distinct ClpS paralogs. Although ClpSl is typical of bacterial ClpS, ClpS2 differs in crucial ways. ClpS2 in Synechococcus elongatus is a relatively low-abundant, soluble protein essential for phototrophic growth. Like ClpSl, ClpS2 binds to the ClpCP3/R protease to block α-casein degradation and promote that of N-end rule substrates in vitro. However, their substrate specificity differs, with ClpSl recognizing destabilizing Phe and Tyr residues at the substrate N-terminus whereas ClpS2 recognizes Leu. Overall, ClpS2 appears to have independently evolved in cyanobacteria to degrade a particular group of proteins, whose turnover is vital for cell viability.
Gesehen am 06.07.2020